Exigências nutricionais de cordeiros Santa Inês castrados e não castrados - Lima, Francisco Wellington Rodrigues (2017)
An study was conducted to evaluate the energy and protein requirements for growth and maintenance of castrated and non castrated lambs. Thirty-eight Santa Ines lambs were used with initial body weight (BW) 14.46 ± 1.72 kg and approximately two months old. Four animals of each sex class were slaughtered at the beginning of the experiment as reference group, to obtain body composition and initial empty body weight. The remaining animals were placed in individual pens in a factorial design with three feeding levels (ad libitum, 30 and 60% feed restriction) and two sex classes (castrated and non-castrated), constituting five animals per treatment. The animals where weighed weekly to monitor weight gain, and when animals fed ad libitum reached 30 kg BW, all experimental animals were slaughtered. The adequacy of the Small Ruminant Nutrition System (SRNS) to estimate dry matter intake (DMI) and average daily gain (ADG) was evaluate, as well as the HH section methodology to predict the body chemical composition of the animals. The feed restriction promoted a reduction in the body fat and energy content, while the body protein content was not influenced. The net energy required for gain (NEg) and the net protein required for gain (NPg) were not affected by sex class. The NEg varied from 0.269 a 0.479 Mcal/day, and the NPg varied from 24.57 to 16.33 g/day for lambs with BW of 15 and 30 kg and BWG of 200 g. The metabolizable energy efficiency for gain (kg) was 0.37, and the metabolizable protein efficiency for gain (kpg) was 0.28. The net energy required for maintenance (NEm) and the net requirement of protein for maintenance (NPm) did not differ between castrated and non-castrated lambs, and as estimates at 57.5 kcal/kg PCJ0.75/day and 1.30 g/kg FBW0.75/day, respectively. The metabolizable energy efficiency for maintenance (km) and efficiency of metabolizable protein use for maintenance (kpm) was 0.60 and 0.57, respectively. The SRNS model precisely predicted the DMI and ADG in Santa Ines lambs. The content of water, fat and energy in the carcass and empty body were satisfactorily estimated by the HH section, but there was no precision in the estimation of protein and ash content. The results of the present study indicated that, although body composition differed between castrated and non castrated Santa Ines sheep, the nutritional requirements of energy and protein for maintenance and weight gain were not affected by the sexual class for lambs weighing up to 30 kg BW.